2022
DOI: 10.3390/genes13122290
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of Pseudomonas asiatica JP233: An Efficient Phosphate-Solubilizing Bacterium

Abstract: The bacterium Pseudomonas sp. strain JP233 has been reported to efficiently solubilize sparingly soluble inorganic phosphate, promote plant growth and significantly reduce phosphorus (P) leaching loss from soil. The production of 2-keto gluconic acid (2KGA) by strain JP233 was identified as the main active metabolite responsible for phosphate solubilization. However, the genetic basis of phosphate solubilization and plant-growth promotion remained unclear. As a result, the genome of JP233 was sequenced and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Glucose can form gluconic acid through the synergistic effects of pyrroloquinoline quinine (PQQ) and glucose dehydrogenase (GDH), which dissolves insoluble phosphate ( Jaiswal et al, 2021 ). Pseudomonas produces gluconic acid to increase phosphate solubility, which has become an important technology for improving phosphate fertilizer management in modern agriculture ( Wang et al, 2022 ; Rai et al, 2023 ). Inoculation of Pseudomonas fluorescens and Pseudomonas putida under soluble phosphate-restricted conditions can produce a large amount of gluconic acid, which promotes plant growth ( Jin et al, 2022 ).…”
Section: The P Removal Mechanism Of Psmsmentioning
confidence: 99%
“…Glucose can form gluconic acid through the synergistic effects of pyrroloquinoline quinine (PQQ) and glucose dehydrogenase (GDH), which dissolves insoluble phosphate ( Jaiswal et al, 2021 ). Pseudomonas produces gluconic acid to increase phosphate solubility, which has become an important technology for improving phosphate fertilizer management in modern agriculture ( Wang et al, 2022 ; Rai et al, 2023 ). Inoculation of Pseudomonas fluorescens and Pseudomonas putida under soluble phosphate-restricted conditions can produce a large amount of gluconic acid, which promotes plant growth ( Jin et al, 2022 ).…”
Section: The P Removal Mechanism Of Psmsmentioning
confidence: 99%
“…S119, a gene coding the biosynthesis pathway of gluconic acid. It is also a major member of the group that dissolves insoluble phosphorus in soil [148,149]. Some studies have also found an interaction between AFM and PSB.…”
Section: Bacteria Convert Soil Phosphorus Which Helps Plants To Effec...mentioning
confidence: 99%